2020
DOI: 10.1108/ijot-09-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the acute management of closed intra-articular fractures of the proximal interphalangeal joint in Ireland

Abstract: Purpose Many treatment methods for intra-articular fractures of the proximal interphalangeal (PIP) joint are described in the literature without a consensus on the most effective approach. The purpose of this study was to investigate the methods of treatment of PIP joint fractures being used by trauma surgeons in the Republic of Ireland currently and the timing of referral to therapy. Design/methodology/approach A cross-sectional descriptive study methodology was used to survey trauma surgeons, occupational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…An overall descriptive design (Cresswell, 2014) using a survey format was chosen. Survey methodology provides a useful mechanism for presenting an overview of current interventions to inform practice development and has been used recently in an Irish study of hand therapy practice (Harmon and Spirtos, 2020). The online survey platform, Survey Monkey was used for ease of administration, completion and analysis.…”
Section: Methodsmentioning
confidence: 99%
“…An overall descriptive design (Cresswell, 2014) using a survey format was chosen. Survey methodology provides a useful mechanism for presenting an overview of current interventions to inform practice development and has been used recently in an Irish study of hand therapy practice (Harmon and Spirtos, 2020). The online survey platform, Survey Monkey was used for ease of administration, completion and analysis.…”
Section: Methodsmentioning
confidence: 99%
“…One study investigating the acute management of closed intraarticular fractures of the PIPJ found that joint mobilization and patient education regarding mobilization were the primary reasons for referral to therapy across all levels of fracture severity. 32 Isolated volar plate avulsion injuries are amenable to early mobilization of the PIPJ with progressive ROM exercises provided the joint is stable. 2 Early mobilization for PIPJ fractures is recommended within the first week, and there is agreement in the literature that flexion exercises of the PIPJ should be commenced soon after injury with extension exercises to follow 2e3 weeks post injury.…”
Section: Rehabilitation Of Vpismentioning
confidence: 99%